Remnant creep life estimation approach for Alloy 617 tubes of ultra-supercritical thermal power plants - Yeo W.H.; Fry A.T.; Inayat-Hussain J.I.; Purbolaksono J. (Elsevier Ltd, 2023)
Boilers; Coal; Fossil fuel power plants; High temperature operations; Steam; Steam power plants; Thermoelectric power plants; Tubes (components); Alloy 617; Condition; Creep damages; Creep life; High-temperature operation; Steam pressures; Steam temperature; Supercritical; Thermal-power plants; Ultra-supercritical power plants; Creep